Lamination type proton conductive electrolyte membrane, and method for producing the same

The laminated proton-conductive electrolyte film with a nanosite layer of proton-conductive nanoseats addresses conductivity and permeability issues, ensuring high efficiency and durability in devices like fuel cells.

JP2025014244APending Publication Date: 2025-01-30KK TOYOTA CHUO KENKYUSHO +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023116623
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

Smart Images

  • Figure 2025014244000001_ABST
    Figure 2025014244000001_ABST
Patent Text Reader

Abstract

To provide a proton conductive electrolyte membrane that satisfies both of proton conductivity and gas low permeability.SOLUTION: In a lamination type proton conductive electrolyte membrane, a first electrolyte membrane having proton conductivity, a nano-sheet layer equipped with a proton conductive nano-sheet, and a second electrolyte membrane having proton conductivity are laminated in this order, where the nano-sheet layer is constituted by aggregating a plurality of the proton conductive nano-sheets in a surface direction of the nano-sheet layer, and the proton conductive nano-sheet has proton conductivity in a lamination direction of the nano-sheet layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminated proton-conducting electrolyte membrane and a method for producing the same. [Background technology]

[0002] Conventionally, various proton-conducting electrolyte membranes with suppressed gas permeability for use in energy conversion devices such as water electrolysis devices for producing hydrogen and fuel cells for generating electricity using hydrogen have been proposed. For example, Patent Document 1 discloses a laminated electrolyte membrane having a nanosheet laminated catalyst layer in which a plurality of nanosheet-shaped catalysts made of platinum or the like are laminated between a first electrolyte membrane and a second electrolyte membrane. In addition, Non-Patent Document 1 discloses a laminated electrolyte membrane having a sandwich structure of a single-layer CVD graphene and a proton exchange membrane, and Non-Patent Document 2 and Non-Patent Document 3 disclose a laminated electrolyte membrane having a sandwich structure of a single-layer membrane of hexagonal boron nitride (h-BN) and a proton exchange membrane. In such a laminated electrolyte membrane, the crossover of hydrogen and oxygen in the laminated electrolyte membrane is suppressed by providing a nanosheet laminated catalyst layer, a single-layer CVD graphene, a single-layer membrane of h-BN, or the like. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-167619 A [Non-patent literature]

[0004] [Non-Patent Document 1] Single-Layer Graphene Sandwiched between Proton-Exchange Membranes for Selective Proton Transmission, ACS Appl. Nano Mater., 2019, 2, 964-974 [Non-Patent Document 2] Sandwiching h-BN Monolayer Films between Sulfonated Poly(ether ether ketone) and Nafion for Proton Exchange Membranes with Improved Ion Selectivity, Acs Nano, 2019, 13, 2094-2102 [Non-Patent Document 3] AA'-Stacked Trilayer Hexagonal Boron Nitride Membrane for Proton Exchange Membrane Fuel Cells, ACS Nano, 2018, 12, 10764-10771 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the above-mentioned laminated electrolyte membrane, although hydrogen crossover is suppressed by providing a nanosheet laminated catalyst layer, a single-layer CVD graphene, a single-layer membrane of h-BN, etc., the proton conductivity of the entire laminated electrolyte membrane is suppressed by the nanosheet laminated catalyst layer, the single-layer CVD graphene, the single-layer membrane of h-BN, etc., and there is a possibility that a problem of an increase in the resistance of the electrolyte membrane may occur. For example, the nanosheet laminated catalyst layer disclosed in Patent Document 1 does not have substantial proton conductivity, so that the proton conductivity of the entire laminated electrolyte membrane is reduced by providing such a nanosheet laminated catalyst layer. In addition, the single-layer CVD graphene and the single-layer membrane of h-BN disclosed in Non-Patent Documents 1-3 have a certain degree of proton conductivity, but it is difficult to say that the suppression of the decrease in proton conductivity of the entire laminated electrolyte membrane is sufficient.

[0006] Furthermore, the nanosheet laminated catalyst layer disclosed in Patent Document 1 converts hydrogen and oxygen that have entered the laminated electrolyte membrane into water through the chemical reaction "H2+1 / 2O2→H2O," thereby suppressing hydrogen crossover. However, this reaction consumes hydrogen. As a result, there has been a problem of reduced reaction efficiency in devices such as water electrolysis devices and fuel cells that are equipped with such laminated electrolyte membranes. For this reason, a proton-conducting electrolyte membrane that achieves both proton conductivity and low gas permeability while also providing a proton-conducting electrolyte membrane that is equipped with the proton-conducting electrolyte membrane has been developed. Therefore, there has been a demand for technology that can suppress the decrease in reaction efficiency in such an apparatus. [Means for solving the problem]

[0007] The present disclosure can be realized in the following forms. (1) According to one embodiment of the present disclosure, there is provided a laminated proton-conductive electrolyte membrane, which comprises a first electrolyte membrane having proton conductivity, a nanosheet layer having a proton-conductive nanosheet, and a second electrolyte membrane having proton conductivity laminated in this order, the nanosheet layer being constituted by an assembly of a plurality of the proton-conductive nanosheets in the plane direction of the nanosheet layer, and the proton-conductive nanosheets having proton conductivity in the lamination direction of the nanosheet layer. According to this type of laminated proton-conductive electrolyte membrane, a nanosheet layer is provided between the first electrolyte membrane and the second electrolyte membrane, which is constituted by a plurality of proton-conductive nanosheets assembled in the planar direction, and therefore the proton-conductive electrolyte membrane can achieve both proton conductivity and low gas permeability. In addition, since the proton-conductive nanosheet does not substantially have catalytic activity for reacting hydrogen with oxygen, it is possible to suppress a decrease in reaction efficiency in a device equipped with the laminated proton-conductive electrolyte membrane. (2) In the laminated proton-conductive electrolyte membrane of the above embodiment, the proton-conductive nanosheet may be at least one selected from a graphene nanosheet, a graphene oxide nanosheet, a silicate nanosheet, an h-BN nanosheet, and a nitrogen-doped graphene nanosheet. With this configuration, the effect of ensuring the proton conductivity of the laminated proton-conductive electrolyte membrane can be enhanced. (3) In the laminated proton-conductive electrolyte membrane of the above embodiment, when the proton conductivity is measured under conditions of room temperature and a relative humidity of 100% RH, the proton conductivity σ in the lamination direction of the laminated proton-conductive electrolyte membrane is nano and a proton conductivity σ in the lamination direction of a joined electrolyte membrane in which the first electrolyte membrane and the second electrolyte membrane are joined without the nanosheet layer. comp1 When comparing with,σ comp1 σ for nano and the proton conductivity σ nano and a proton conductivity σ in the thickness direction of a single-layer electrolyte membrane which is the same type of electrolyte membrane as the first electrolyte membrane and the second electrolyte membrane and has a thickness equal to the total thickness of the first electrolyte membrane and the second electrolyte membrane. comp2 When comparing with,σ comp2 σ for nano and the gas permeability coefficient P of the laminated proton-conductive electrolyte membrane is 80% or more when the gas permeability coefficient is measured under the conditions of room temperature, relative humidity 0% RH, and differential pressure 100 kPa. nano and the gas permeability coefficient P of the bonded electrolyte membrane comp1 When comparing with,P comp1 P for nano and the gas permeability coefficient P nano and the gas permeability coefficient P of the monolayer electrolyte membrane comp2 When comparing with,P comp2 P for nano and (b) the ratio of at least one of them may be 75% or less. With this configuration, the effect of achieving both proton conductivity and low gas permeability in the proton conducting electrolyte membrane can be enhanced. (4) In the laminated proton conductive electrolyte membrane of the above embodiment, the aspect ratio, which is the ratio of the average particle size of the proton conductive nanosheet to the thickness of the nanosheet, is 10 to 10 7 With such a configuration, the effect of achieving both proton conductivity and low gas permeability in the proton conducting electrolyte membrane can be enhanced. (5) In the laminated proton-conducting electrolyte membrane of the above embodiment, the coverage, which is the ratio of the area of ​​the portion covered by the nanosheet layer to the area of ​​the surface of the first electrolyte membrane, may be 70% or more and 99.9% or less. With this configuration, the effect of achieving both proton conductivity and low gas permeability in the proton-conducting electrolyte membrane can be enhanced. (6) According to another aspect of the present disclosure, there is provided a method for producing a laminated proton-conductive electrolyte membrane material, the method for producing a laminated proton-conductive electrolyte membrane includes preparing a dispersion of a proton-conductive nanosheet, and applying the dispersion onto one of a first electrolyte membrane having proton conductivity and a second electrolyte membrane having proton conductivity while heating the one electrolyte membrane. After dropping the dispersion liquid, the dropped dispersion liquid is removed from one of the electrolyte membranes and the one of the electrolyte membranes is dried, thereby forming a nanosheet layer comprising the proton-conductive nanosheet on one of the electrolyte membranes, and the other of the first electrolyte membrane and the second electrolyte membrane is laminated and bonded on the nanosheet layer. According to this embodiment of the method for producing a laminated proton-conductive electrolyte membrane, the laminated proton-conductive electrolyte membrane described in (1) above can be produced by a very simple operation. The present disclosure may be realized in various forms other than those described above, for example, a water electrolysis cell including a stacked proton-conductive electrolyte membrane, a water electrolysis device including a water electrolysis cell, a fuel cell including a stacked proton-conductive electrolyte membrane, a fuel cell including a fuel cell cell, etc. [Brief description of the drawings]

[0008] [Figure 1]FIG. 1 is a cross-sectional view illustrating a schematic configuration of a laminated proton-conductive electrolyte membrane. [Diagram 2] 1A to 1C are explanatory diagrams showing a method for producing a laminated proton-conducting electrolyte membrane. [Diagram 3] FIG. 1 is an explanatory diagram illustrating the configuration and measurement results of each sample. [Figure 4] FIG. 2 is an explanatory diagram that illustrates a schematic view of the coating state of a nanocoat region. [Diagram 5] FIG. 2 is an explanatory diagram showing a micrograph obtained by a 3D measuring laser microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A. Structure of the laminated proton-conducting electrolyte membrane: 1 is a cross-sectional view that shows a schematic configuration of a laminated proton-conductive electrolyte membrane 10 according to an embodiment of the present disclosure. The laminated proton-conductive electrolyte membrane 10 is formed by laminating a first electrolyte membrane 12, a nanosheet layer 16, and a second electrolyte membrane 14 in this order.

[0010] (A-1) Electrolyte membrane: The first electrolyte membrane 12 and the second electrolyte membrane 14 are electrolyte membranes having proton conductivity. The first electrolyte membrane 12 and the second electrolyte membrane 14 may be solid polymer electrolyte membranes, and are not particularly limited as long as they have proton conductivity. Specifically, the first electrolyte membrane 12 and the second electrolyte membrane 14 may be various ion exchange membranes made of, for example, fluorine-based resins such as perfluorocarbon sulfonic acid polymers, or hydrocarbon-based resins in which ion exchange groups are introduced into polyether ether ketone (PEEK), etc. The first electrolyte membrane 12 and the second electrolyte membrane 14 may be the same type of electrolyte membrane or different types of electrolyte membranes.

[0011] (A-2) Proton conductive nanosheet: The nanosheet layer 16 includes a proton-conductive nanosheet. Here, a "nanosheet" refers to a sheet-like nanomaterial having a thickness of about 0.1 to 100 nm, and the nanosheet layer 16 is configured by assembling a plurality of proton-conductive nanosheets in the planar direction of the nanosheet layer 16.

[0012] The proton conductive nanosheet constituting the nanosheet layer 16 of this embodiment exhibits proton conductivity in the thickness direction of the nanosheet layer 16, and as a result, the nanosheet layer 16 also exhibits proton conductivity in the thickness direction. There are no particular limitations on the proton conductive nanosheet constituting the nanosheet layer 16, so long as it can be arranged so as to exhibit proton conductivity in the thickness direction of the nanosheet layer 16. Examples of the proton conductive nanosheet include two-dimensional substances such as graphene nanosheets and h-BN (hexagonal boron nitride) nanosheets, or graphene oxide nanosheets and nitrogen-doped graphene nanosheets obtained by partially modifying, introducing defects, or introducing functional groups into these. In addition, silicate nanosheets (e.g., having a thickness of about 1 nm) that form unit layers of minerals called layered silicate minerals, such as vermiculite, may also be used. These The nanosheet layer 16 can be formed using at least one of the proton conductive nanosheets. Proton conductive nanosheets are a group of two-dimensional substances having a basic structure consisting of one atomic layer. These proton conductive nanosheets are characterized by having pores that allow only protons to pass through them, and their proton conductivity has been measured and reported using the proton pump method or the like. In other words, a "proton conductive nanosheet" can be said to be "a material having fine through-holes that allow only protons to pass through, among two-dimensional sheet-like substances having a thickness on the order of sub-nanometers to nanometers."

[0013] A proton conductive nanosheet is composed of atoms arranged regularly two-dimensionally. Among the above-mentioned proton conductive nanosheets, for example, a graphene oxide nanosheet and a nitrogen-doped graphene nanosheet are formed by arranging carbon atoms two-dimensionally in a hexagonal lattice shape. In addition, an h-BN nanosheet (hexagonal boron nitride nanosheet) is formed by arranging boron atoms and nitrogen atoms two-dimensionally in a hexagonal lattice shape. That is, these proton conductive nanosheets form a six-membered ring network, which is a two-dimensional structure with six-membered rings as units. The proton conductive nanosheets described above have through holes (for example, holes formed by the above-mentioned hexagonal lattice in the graphene oxide nanosheet) that penetrate the proton conductive nanosheet in the thickness direction by the constituent atoms being arranged regularly two-dimensionally. By having such ultrafine through holes such as six-membered rings, the proton conductive nanosheet exhibits proton conductivity in the thickness direction. However, since the size of such through holes is smaller than that of hydrogen molecules, gas molecules cannot pass through the proton conductive nanosheet via the through holes. Therefore, the nanosheet layer 16 formed by assembling a plurality of proton-conductive nanosheets in the planar direction can exhibit gas barrier properties that prevent gas from passing in the thickness direction of the nanosheet layer 16. As described above, it can be said that proton-conductive nanosheets, which are two-dimensional sheet-like substances having fine through-holes that only allow protons to pass through, do not substantially have hydrogen-oxygen recombination activity. Therefore, it can be said that proton-conductive nanosheets do not substantially have catalytic activity that promotes the reaction between hydrogen and oxygen.

[0014] In the proton conductive nanosheet of this embodiment, the aspect ratio is 10 to 10 7It is preferable that the aspect ratio is 1 / 1000. When the thickness is fixed, the larger the aspect ratio, the easier it is to improve the gas barrier properties of the nanosheet layer 16, and the more difficult it is to ensure the dispersibility of the proton conductive nanosheet in water or an organic solvent. When the thickness is fixed, the smaller the aspect ratio, the easier it is to improve the proton conductivity of the nanosheet layer 16. Here, the "aspect ratio (AR)" is a value calculated by the following formula (1). In the formula (1), D [nm] indicates the "average particle size of the proton conductive nanosheet", and t [nm] indicates the "average thickness of the proton conductive nanosheet". In this embodiment, the "average thickness of the proton conductive nanosheet" refers to the measured thickness of the proton conductive nanosheet that is actually obtained, and is not necessarily the thickness of the proton conductive nanosheet in a single layer state. Specifically, when a proton conductive nanosheet that can obtain a nearly single layer nanosheet, such as a graphene oxide nanosheet, is used as the proton conductive nanosheet, the measured value of the thickness of such a nearly single layer nanosheet is used. In contrast, when a proton conductive nanosheet obtained in a multi-layered state, such as a silicate nanosheet, is used as the proton conductive nanosheet, the measured thickness of such a nanosheet in a multi-layered state is used.

[0015] AR = D / t … (1)

[0016] The average particle diameter D of the proton conductive nanosheets can be obtained by preparing a dispersion of the proton conductive nanosheets and measuring the dispersion by dynamic light scattering. To measure the aspect ratio of the proton conductive nanosheets contained in the laminated proton conductive electrolyte membrane 10, a solvent (e.g., For example, when the electrolyte membrane is made of perfluorocarbon sulfonic acid polymer, the laminated proton-conductive electrolyte membrane 10 is placed in an alcohol aqueous solution or the like to dissolve the electrolyte membrane, and then the proton-conductive nanosheet is recovered from the liquid and measured.

[0017] (A-3) Nanosheet layer: As described above, the nanosheet layer 16 provided between the first electrolyte membrane 12 and the second electrolyte membrane 14 is configured by assembling a plurality of proton conductive nanosheets in the plane direction of the nanosheet layer 16. Here, the nanosheet layer 16 is not formed as a completely dense membrane, and may have some defects, i.e., grain boundary defects and uncovered portions that do not cover the electrolyte membrane surface. When the degree of denseness in the nanosheet layer 16 is high, the coverage, which is the ratio of the area of ​​the portion covered by the nanosheet layer 16 to the area of ​​the surface of one of the electrolyte membranes (for example, the first electrolyte membrane 12) of the pair of electrolyte membranes, becomes large. Therefore, the higher the coverage, the higher the gas impermeability of the laminated proton conductive electrolyte membrane 10 can be. From the viewpoint of ensuring low gas permeability of the laminated proton conductive electrolyte membrane 10, the coverage is preferably, for example, 30% or more, more preferably 50% or more, and even more preferably 70% or more.

[0018] However, the portion of the surface of the first electrolyte membrane 12 that is not covered by the nanosheet layer 16 is a portion where proton conduction is not hindered by the nanosheet layer 16 due to the first electrolyte membrane 12 and the second electrolyte membrane 14 being in direct contact with each other, etc. A proton-conducting nanosheet generally has lower proton conductivity than the electrolyte constituting the first electrolyte membrane 12 and the second electrolyte membrane 14, so that the portion where the first electrolyte membrane 12 and the second electrolyte membrane 14 are in direct contact with each other has higher proton conductivity than the portion where the nanosheet layer 16 is interposed. Therefore, the nanosheet layer 16 has defects as described above, thereby increasing the proton conductivity of the entire laminated proton-conducting electrolyte membrane 10. The coverage can be, for example, 99.9% or less, and from the viewpoint of increasing the proton conductivity of the entire laminated proton-conducting electrolyte membrane 10, the coverage is preferably 95% or less, more preferably 90% or less, and even more preferably 85% or less. The above coverage rate may be appropriately set according to the type of electrolyte and proton conductive nanosheet used from the viewpoint of ensuring low gas permeability and proton conductivity of the entire laminated proton conductive electrolyte membrane 10. The fact that the nanosheet layer 16 is formed by accumulating a plurality of proton conductive nanosheets can be confirmed by observing the grain boundaries by two-dimensional mapping using a laser Raman microscope or the like, for example.

[0019] In the nanosheet layer 16, as described above, a plurality of proton conductive nanosheets are assembled in the plane direction of the nanosheet layer 16, but a plurality of proton conductive nanosheets may be laminated in the thickness direction of the nanosheet layer 16. That is, the nanosheet layer 16 may be a monolayer film of a proton conductive nanosheet (a monolayer sheet of proton conductive nanosheet molecules arranged two-dimensionally), or may be a film in which a plurality of proton conductive nanosheets are laminated in the thickness direction in at least a part of the nanosheet layer 16. For example, when a graphene nanosheet, an h-BN nanosheet, a graphene oxide nanosheet, or a nitrogen-doped graphene nanosheet is used, the nanosheet layer 16 can basically be formed as a monolayer film. In addition, when a silicate nanosheet is used, the nanosheet layer 16 is usually formed as a multilayer film. By laminating a plurality of proton conductive nanosheets in the thickness direction in at least a part of the nanosheet layer 16, the effect of improving the gas barrier property by providing the nanosheet layer 16 can be enhanced.

[0020] In the laminated proton-conductive electrolyte membrane 10 in which the nanosheet layer 16 is provided between the first electrolyte membrane 12 and the second electrolyte membrane 14, the proton conductivity in the lamination direction is preferably 60 mS / cm or more, more preferably 63 mS / cm or more, and more preferably 65 mS / cm or more. It is even more desirable that the proton conductivity be equal to or higher than the above. In other words, it is desirable that the above-mentioned proton conductivity can be ensured in the laminated proton-conducting electrolyte membrane 10 even if the nanosheet layer 16 is provided. In the following explanation, "proton conductivity" refers to a value measured under conditions of room temperature and a relative humidity of 100% RH. The proton conductivity σ [mS / cm] is a value calculated by the following formula (2). In formula (2), R [Ω] indicates the resistance value, A [cm 2 ] indicates the electrode area in the evaluation cell for measuring the proton conductivity, and L [cm] indicates the thickness of the laminated proton-conducting electrolyte membrane. A specific method for measuring the proton conductivity σ will be described in detail later.

[0021] σ=L / (R·A)×1000 … (2)

[0022] Here, the proton conductivity of the laminated proton-conducting electrolyte membrane 10 of the embodiment having the nanosheet layer 16 is expressed as σ nano The proton conductivity of the electrolyte membrane in which the first electrolyte membrane 12 and the second electrolyte membrane 14 are joined without providing the nanosheet layer 16 (hereinafter, also referred to as the "jointed electrolyte membrane") is σ comp1 In this case, σ nano and σ comp1 Proton conductivity σ comp1 σ for nano The ratio is desirably 80% or more, more desirably 85% or more, and even more desirably 90% or more. The bonding of the first electrolyte membrane 12 and the second electrolyte membrane 14 in the bonded electrolyte membrane may be performed by a method in which the first electrolyte membrane 12 and the second electrolyte membrane 14 are directly bonded to each other without providing a layer for bonding between the first electrolyte membrane 12 and the second electrolyte membrane 14, and may be, for example, hot pressing.

[0023] In addition, the proton conductivity in the thickness direction of an electrolyte membrane (hereinafter also referred to as a "single-layer electrolyte membrane") that is the same type as the first electrolyte membrane 12 and the second electrolyte membrane 14 and has a thickness equal to the total thickness of the first electrolyte membrane 12 and the second electrolyte membrane 14 is defined as σ comp2 In this case, σ nano and σ comp2 Proton conductivity σ comp2 σ for nano The ratio of is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. That is, the above-mentioned proton conductivity σ comp1 σ for nano and the proton conductivity σ comp2 σ for nano It is desirable that at least one of the ratios is 80% or more. It is desirable that the above-mentioned ratio values ​​related to the proton conductivity are widely satisfied under the conditions under which the laminated proton conducting electrolyte membrane 10 is used.

[0024] The laminated proton-conductive electrolyte membrane 10 has a gas permeability coefficient of 4.0 mol m / m 2 s Pa or less, and 3.8 mol m / m 2 s Pa or less, and 3.6 mol m / m 2 It is more desirable that the gas permeability coefficient is equal to or less than 1 s Pa. In the following description, the "gas permeability coefficient" refers to a value measured under conditions of room temperature, relative humidity of 0% RH, and differential pressure of 100 kPa.

[0025] Here, the gas permeability coefficient of the laminated proton-conductive electrolyte membrane 10 of the embodiment having the nanosheet layer 16 is defined as P nano The gas permeability coefficient of the bonded electrolyte membrane is P comp1 In this case, P nano and P comp1 The gas permeability coefficient P comp1 P for nano The ratio is preferably 75% or less, more preferably 70% or less. In addition, the gas permeability coefficient of the above-mentioned single-layer electrolyte membrane is P comp2 In this case, P nano and P comp2 The gas permeability coefficient P comp2 P for nano The ratio is preferably 75% or less, and more preferably 70% or less. That is, the above-mentioned gas permeability coefficient P comp1 P for nano and the gas permeability coefficient P comp2 P for nano It is desirable that at least one of the ratios is 75% or less. The ratio values ​​related to the gas permeability coefficient described above are widely applicable under the conditions in which the laminated proton conducting electrolyte membrane 10 is used. It is desirable to fulfill this requirement.

[0026] B. Manufacturing method of laminated proton-conducting electrolyte membrane: 2 is an explanatory diagram showing a method for producing the laminated proton conductive electrolyte membrane 10 of this embodiment. The method for producing the laminated proton conductive electrolyte membrane 10 of this embodiment roughly comprises three steps: (1) a nanosheet dispersion preparation step (step T100), (2) a nanocoating step for the electrolyte membrane surface (steps T110, T120), and (3) a laminated electrolyte membrane preparation step (step T130). Each step will be described below in order.

[0027] (B-1) Nanosheet dispersion preparation process: When manufacturing the laminated proton-conductive electrolyte membrane 10, first, a dispersion of a proton-conductive nanosheet for forming the nanosheet layer 16 is prepared (step T100). The dispersion of the proton-conductive nanosheet is prepared by dispersing the proton-conductive nanosheet constituting the nanosheet layer 16 in a dispersion medium. The proton-conductive nanosheet used is obtained, for example, by peeling the nanosheet from a layered compound that is the material of the proton-conductive nanosheet. For example, water can be used as the dispersion medium. The dispersion medium may be any liquid that does not substantially react with the proton-conductive nanosheet or the electrolyte membrane and allows the self-organization of the proton-conductive nanosheet described below to proceed without hindrance. At this time, as a dispersion treatment for dispersing the proton-conductive nanosheet in the dispersion medium, for example, a treatment such as shaking, ultrasonic treatment, stirring, or mixing using a mixer can be adopted. By performing the treatment for dispersing the proton-conductive nanosheet in the dispersion medium as described above, a dispersion in which the proton-conductive two-dimensional material and the proton-conductive nanosheet are dispersed in the dispersion medium can be obtained. Here, when a nanosheet having a relatively high hydrophobicity, such as a silicate nanosheet, is used as the proton conductive nanosheet, it is desirable to forcibly increase the dispersibility of the proton conductive nanosheet in the dispersion liquid by ultrasonic treatment or the like.

[0028] Thereafter, a process is performed to separate a portion containing a proton conductive nanosheet having a single layer or several layers from the liquid that has been subjected to the above dispersion process. As such a separation process, a process such as centrifugation or decantation can be adopted. After separating the liquid containing the proton conductive nanosheet, an auxiliary agent for realizing a dense nanosheet layer 16 is added to the separated liquid as necessary to complete a nanosheet dispersion liquid, which is a dispersion liquid for film formation. As the auxiliary agent to be added, for example, a surfactant (e.g., tetraalkylammonium salts such as tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, etc.) or an alcohol that can be mixed with water (e.g., ethanol, methanol, propanol, butanol, etc.) can be used.

[0029] By adding alcohols such as ethanol to the nanosheet dispersion, the viscosity of the dispersion can be reduced, and when convection is caused in the dispersion by heating during the formation of the nanosheet layer 16 described later, the movement of the nanosheets for packing the proton conductive nanosheets can be facilitated. Furthermore, by adding the above-mentioned alcohols to the dispersion, the surface tension of the dispersion and the evaporation rate in the subsequent heating process can also be adjusted. In addition, when a nanosheet having a certain degree of hydrophilic group such as graphene oxide is used as the proton conductive nanosheet, it is desirable to add a surfactant such as the above-mentioned tetrabutylammonium salt (TBA) to the dispersion to hydrophobize the particle surface of the nanosheet, thereby reducing the surface tension of the dispersion. Note that the above-mentioned dispersion treatment such as ultrasonic treatment, addition of a surfactant, and addition of alcohols are not essential, and the conditions for preparing the dispersion can be appropriately set according to the proton conductive nanosheet to be used.

[0030] (B-2) Nanocoating process for the electrolyte membrane surface: Next, the surface of one of the first electrolyte membrane 12 and the second electrolyte membrane 14 is coated with the nanosheet dispersion obtained in step T100. Specifically, the nanosheet dispersion is dropped onto the one electrolyte membrane (step T110), and then the dropped liquid is removed from the electrolyte membrane to dry the electrolyte membrane (step T120). The dropped dispersion can be removed by suction removal, for example, by sucking up the dispersion with a pipette. When the dispersion in which the proton-conductive nanosheets are dispersed as described above is dropped onto the electrolyte membrane, the proton-conductive nanosheets are densified to reduce the surface free energy (surface tension) at the interface between the air and the dispersion. By utilizing such self-organization, a uniform nanosheet layer 16 can be formed on the electrolyte membrane.

[0031] In the above-mentioned steps T110 and T120, the electrolyte membrane is heated (for example, at about 90 to 130° C.) when the dispersion liquid is dropped onto the electrolyte membrane and absorbed. It is believed that such heating of the electrolyte membrane causes convection in the dropped dispersion liquid, and the proton conductive nanosheets can be moved and aligned on the electrolyte membrane. In addition, the packing (densification) of the nanosheets by the above-mentioned self-organization is due to a physical phenomenon that reduces the surface free energy, and therefore, it can be said that it is a phenomenon that progresses by dropping the dispersion liquid, regardless of the type of proton conductive nanosheet or electrolyte membrane used.

[0032] Here, the coverage of the nanosheet layer 16 on the electrolyte membrane and the number of nanosheet layers in the nanosheet layer 16 (the number of proton conductive nanosheets arranged in a layered manner in the thickness direction) can be adjusted by the concentration of the dispersion liquid when the nanosheet dispersion liquid is dropped, the time until the dropped dispersion liquid is removed, etc. For example, by appropriately setting the concentration of the dispersion liquid described above and the time from dropping to removal, etc., it is possible to form a nanosheet layer 16 composed of a single layer of nanosheets, and by repeating the operation set for forming a single nanosheet layer 16, it is possible to form a nanosheet layer 16 in which multiple layers (any number of layers) are laminated.

[0033] (B-3) Manufacturing process of laminated electrolyte membrane: After forming the nanosheet layer 16 on one electrolyte membrane, the other electrolyte membrane is laminated and bonded onto the formed nanosheet layer 16 to complete the laminated proton-conducting electrolyte membrane 10 (step T130). The nanosheet layer 16 and the other electrolyte membrane can be bonded by, for example, hot pressing.

[0034] C. Application examples of laminated proton-conducting electrolyte membranes: The laminated proton-conducting electrolyte membrane 10 of the present embodiment can be used, for example, as an electrolyte membrane provided in a polymer electrolyte water electrolysis cell or an electrolyte membrane provided in a polymer electrolyte fuel cell.

[0035] When constructing a water electrolysis cell, an anode is formed on one surface of the laminated proton conducting electrolyte membrane 10, and a cathode is formed on the other surface. In such a water electrolysis cell, when a voltage is applied between the two electrodes, the reaction of the following formula (3) proceeds at the anode, and the reaction of the following formula (4) proceeds at the cathode, generating hydrogen and oxygen through water electrolysis. At this time, protons move from the anode side to the cathode side in the laminated proton conducting electrolyte membrane 10. A water electrolysis device is generally constructed by stacking a plurality of water electrolysis cells such as those described above.

[0036] H2O → 2H + + 1 / 2O2+ 2e - … (3) 2H + + 2e - → H2… (4)

[0037] When constructing a fuel cell, a proton conductive electrolyte membrane 10 is laminated on one side thereof. An anode is formed on the other side, and a cathode is formed on the other side. In such a fuel cell, by supplying a hydrogen-containing gas to the anode side and an oxygen-containing gas to the cathode side and connecting both electrodes to a load, the reaction of the following formula (5) proceeds at the anode and the reaction of the following formula (6) proceeds at the cathode, generating electricity. At this time, protons move from the anode side to the cathode side in the laminated proton-conducting electrolyte membrane 10. A fuel cell device is generally constructed by stacking a plurality of fuel cell cells as described above.

[0038] H2 → 2H + + 2e - … (5) 2H + + 1 / 2O2+ 2e - → H2O … (6)

[0039] According to the laminated proton-conductive electrolyte membrane 10 of the embodiment configured as described above, proton conductivity and low gas permeability can be achieved at the same time, and both proton conductivity and low gas permeability can be secured at a higher level. That is, by disposing the nanosheet layer 16 formed by assembling a plurality of gas-impermeable proton-conductive nanosheets in the plane direction between the first electrolyte membrane 12 and the second electrolyte membrane 14, the gas impermeability of the entire laminated proton-conductive electrolyte membrane 10 can be increased. In addition, by configuring the nanosheet layer 16 interposed between the first electrolyte membrane 12 and the second electrolyte membrane 14 using a proton-conductive nanosheet, it is possible to suppress the decrease in proton conductivity caused by providing the nanosheet layer 16 in the laminated proton-conductive electrolyte membrane 10. In particular, when the nanosheet layer 16 is formed as a layer having some defects such as grain boundary defects and uncovered portions, rather than being formed as a completely dense membrane, it becomes easier to ensure the proton conductivity in the nanosheet layer 16. In addition, the proton-conductive nanosheets constituting the nanosheet layer 16 are two-dimensional material aggregates having through-holes that realize proton conductivity, and do not substantially have catalytic activity for reacting hydrogen with oxygen. Therefore, in the laminated proton-conductive electrolyte membrane 10, while achieving both proton conductivity and low gas permeability, it is possible to suppress a decrease in reaction efficiency in a device equipped with such a laminated proton-conductive electrolyte membrane 10. In addition, when using a large-area nanosheet such as the single-layer CVD graphene or single-layer membrane of h-BN described in Non-Patent Documents 1-3, the nanosheet may be damaged due to wet-dry deformation or the like. In contrast, the nanosheet layer 16 of the embodiment is composed of smaller nanosheets accumulated, and therefore has excellent flexibility and conformability, and the durability of the nanosheet layer 16 can be improved.

[0040] In addition, by constructing a water electrolysis cell or a fuel cell using the laminated proton conductive electrolyte membrane 10 with improved gas impermeability, for example, in a water electrolysis cell, the permeation of hydrogen from the cathode side to the anode side through the electrolyte membrane is suppressed, and the decrease in hydrogen generation efficiency due to hydrogen consumption can be suppressed, and the electrolysis efficiency and electrolyte output can be improved. Furthermore, by improving the hydrogen barrier property of the electrolyte membrane, the hydrogen concentration mixed with oxygen on the anode side can be prevented from reaching the explosion limit concentration, and safety can be improved. In addition, in a fuel cell, the permeation of hydrogen and oxygen through the electrolyte membrane is suppressed, and the decrease in power generation efficiency, the decrease in fuel utilization efficiency due to hydrogen consumption, and the decrease in electromotive force due to the decrease in the cathode potential can be suppressed. Furthermore, since the generation of hydrogen peroxide at the anode caused by oxygen permeating the electrolyte membrane can be suppressed, chemical deterioration of the electrolyte membrane can be suppressed and durability can be improved. In addition, since it is possible to thin the electrolyte membrane while maintaining the gas barrier property, it is possible to reduce the proton conduction resistance overvoltage, thereby enabling high efficiency and high output. Furthermore, by ensuring high proton conductivity in the laminated proton-conducting electrolyte membrane 10, high performance as a water electrolysis cell or a fuel cell is ensured.

[0041] Furthermore, in the laminated proton-conductive electrolyte membrane 10 of this embodiment, as shown in FIG. 2, a nanosheet dispersion liquid is dropped onto one electrolyte membrane, and then the dropped dispersion liquid is absorbed and formed into the electrolyte. The nanosheet layer 16 can be produced by a very simple operation of drying the membrane. Specifically, a complicated membrane-forming process or a large-scale membrane-forming device, such as that required for growing a membrane by a deposition method, is not required. Therefore, for example, the effect of facilitating mass production of the laminated proton-conducting electrolyte membrane 10 can be obtained. In addition, the coverage of the nanosheet layer 16 and the number of nanosheet layers constituting the nanosheet layer 16 can be adjusted by the concentration of the dispersion liquid to be dropped, the amount of the dispersion liquid to be dropped, or the time until the dropped dispersion liquid is removed. Therefore, the nanosheet layer 16 of the desired shape can be produced by a simple operation. EXAMPLES

[0042] Four types of samples, Samples S1 to S4, were fabricated as the laminated proton-conductive electrolyte membranes described below. In each sample, an electrolyte membrane made of perfluorocarbon sulfonic acid polymer was used as the electrolyte membrane (first electrolyte membrane 12 and second electrolyte membrane 14).

[0043] FIG. 3 shows the configurations and measurement results of each of the samples S1 to S4, specifically, the type of nanosheet constituting the nanosheet layer 16, the coverage, the proton conductivity, and the proton conductivity σ copm σ for nano The ratio of gas permeability coefficient, the gas permeability coefficient P copm P for nano 3 is an explanatory diagram showing the ratio of the surface area of ​​the proton conductive nanosheet and the aspect ratio. As shown in Fig. 3, samples S1 and S2 use a graphene oxide nanosheet as the proton conductive nanosheet, and sample S3 uses a silicate nanosheet as the proton conductive nanosheet. Sample S4 is a comparative sample formed by bonding two electrolyte membranes and does not have a nanosheet layer 16.

[0044] [Preparation of laminated proton-conducting electrolyte membrane] (Sample S1) In the nanosheet dispersion preparation process, a commercially available graphene oxide dispersion, G0557 manufactured by Tokyo Chemical Industry Co., Ltd., was used as a material. This graphene oxide dispersion is an aqueous dispersion containing graphene oxide with a concentration of 10 mg / mL and an average particle size of 10-30 μm (catalog value: average 20 μm), in which the graphene oxide is sufficiently peeled off and has relatively high dispersibility. The commercially available dispersion was further treated by the following method to prepare a nanosheet dispersion as a film-forming dispersion.

[0045] First, 1 mL of the above-mentioned commercially available dispersion liquid and 9 mL of water were added to a test tube and mixed, and then centrifuged at 6000 rpm for 30 minutes. After centrifugation, 5 mL of the supernatant liquid was removed with a pipette. The test tube was then shaken and mixed to resuspend the remaining precipitate and liquid, and centrifuged at 2000 rpm for another 30 minutes. 50 μL of the obtained supernatant liquid, 5 mL of water, 60 μL of ethanol, and 0.5 μL of a 10% aqueous solution of tetrabutylammonium hydroxide (TBA) (manufactured by Tokyo Chemical Industry Co., Ltd.) were added and mixed, respectively, to prepare a nanosheet dispersion liquid.

[0046] In the nanocoating process for the electrolyte membrane surface, a Nafion membrane NRE-211 (film thickness 25.4 μm) (Nafion is a registered trademark) was used as the electrolyte membrane. The Nafion membrane was heated on a hot plate at 120° C. for 3 minutes, and 200 μL of the nanosheet dispersion was dropped onto the Nafion membrane. The dropped dispersion was then slowly sucked up, thereby nanocoating the electrolyte membrane surface with graphene oxide and forming a nanosheet layer 16.

[0047] In the laminated electrolyte membrane preparation process, another electrolyte membrane, Nafion membrane NRE-211 (film thickness 25.4 μm) (Nafion is a registered trademark), was superimposed on the surface of the Nafion membrane on which the nanosheet layer 16 was formed, and hot pressed to prepare a laminated proton-conductive electrolyte membrane. The hot pressing conditions were 1 MPa and 140° C. Then, the membrane was washed with a 1M aqueous sulfuric acid solution at 100° C. for 1 hour, and then washed with pure water at 100° C. for 1 hour twice. The laminated proton-conductive electrolyte membrane of sample S1 was obtained by repeating the above steps. The thickness of the nanosheet layer 16 was negligibly thin, and the laminated proton-conductive electrolyte membrane of sample S1 and the laminated proton-conductive electrolyte membranes of samples S2-S4, which will be described later, had a thickness of 50.8 μm.

[0048] (Sample S2) Sample S1 was prepared in the same manner as Sample S1, except that in the nanosheet dispersion preparation process described above, the amount of ethanol added to the supernatant liquid, which is the graphene oxide dispersion liquid, was 200 μL instead of 60 μL.

[0049] (Sample S3) In the nanosheet dispersion preparation process, interlayer ion exchange was first performed on montmorillonite (Kunipia-F, manufactured by Kunimine Industries Co., Ltd.) in order to obtain silicate nanosheets. That is, in order to easily peel off the layers of the silicate nanosheets, ion exchange was performed with Li ions, which are considered to have a higher hydration ability than Na ions. The ion-exchanged montmorillonite was then collected. Specifically, lithium chloride was mixed with 250 mL of pure water to prepare a 1M lithium chloride aqueous solution. 2.16 g of Kunipia-F was mixed with this 1M lithium chloride aqueous solution and stirred at a rotation speed of 200 rpm for 24 hours. A solid was separated from the obtained dispersion using a vacuum filter, and washed by stirring at 1200 rpm for 1 hour in 200 mL of pure water. After repeating this washing, the mixture was stirred with a stirrer at a rotation speed of 300 rpm in 200 mL of pure water to obtain a dispersion. The obtained dispersion was ultrasonically treated for 30 minutes in an ultrasonic cleaner. Then, the mixture was centrifuged at 2000 rpm for 10 minutes in a centrifuge, and the supernatant was collected. 100 μL of the obtained supernatant was mixed with 5 mL of pure water, 60 μL of ethanol, and 2 μL of a 10% aqueous solution of TBA to prepare a nanosheet dispersion containing silicate nanosheets as nanosheets. The average particle size of the silicate nanosheets contained in this dispersion was 4 to 10 μm.

[0050] The step of nano-coating the electrolyte membrane surface and the step of preparing the laminated electrolyte membrane were carried out in the same manner as in Sample S1, to obtain a laminated proton-conductive electrolyte membrane of Sample S3.

[0051] (Sample S4) The electrolyte membrane of sample S3 was produced by bonding together two Nafion membranes NRE-211 (film thickness 25 μm) (Nafion is a registered trademark) without the nanosheet layer 16 and hot pressing them under conditions similar to those of the hot pressing in the laminated electrolyte membrane production process in the manufacturing process for the laminated proton-conductive electrolyte membrane of sample S1.

[0052] [Coverage measurement] The coverage rate was measured for each of the samples S1 to S3 when the nanosheet layer 16 was formed on one electrolyte membrane (hereinafter described as the first electrolyte membrane 12) and before the other electrolyte membrane was superimposed. Here, the coverage state of the nanosheet layer 16 formed on the first electrolyte membrane 12 was observed using a 3D measuring laser microscope (LEXT OLS4000, manufactured by Olympus Corporation) to observe the overlap of the proton conductive nanosheets. The 3D measuring laser microscope is a microscope capable of reconstructing high-resolution images and three-dimensional information. Since the Nafion membrane was soft and had severe irregularities, it was difficult to measure it with an AFM (atomic force microscope), so the coverage state of the nanosheet was observed using the above-mentioned 3D laser microscope, and the coverage rate was calculated. Specifically, a nanosheet region (1.5 cm x 1.5 cm area) was set as the observation target on the surface on which the nanosheet layer 16 was formed, and the coverage rate was calculated as the ratio of the area of ​​the part on which the dense nanosheet layer 16 was formed to the entire nanosheet region.

[0053] As an example, FIG. 4 shows a 1.5 cm 2 nanocoat region set in sample S1. 1 is a schematic diagram of the coating state of an area measuring 1.5 cm × 1.5 cm as observed with a 3D measuring laser microscope. In the figure, the hatched area indicates the area where a dense nanocoat was observed.

[0054] FIG. 5 is an explanatory diagram showing a micrograph obtained by imaging sample S1 with a 3D measuring laser microscope at a magnification of 20 times. In FIG. 5(A) and FIG. 5(B), a scale bar of 100 μm in length is attached. FIG. 5(A) is a photograph of the area shown as region A in FIG. 4 (area where dense nanosheet layer 16 is partially observed), and FIG. 5(B) is a photograph of the area shown as region B in FIG. 4 (area where dense nanosheet layer 16 is observed throughout). As a result of measuring the coverage as described above, as shown in FIG. 3, the coverage of sample S1 was 55%, the coverage of sample S2 was 74%, and the coverage of sample S3 was 30%.

[0055] [Measurement of hydrogen gas permeability coefficient] The gas permeability coefficient of each sample as a laminated proton-conducting electrolyte membrane was measured by the differential pressure method according to JIS K 7126-1 (2006) using a gas permeability measuring device. The principle is to apply a differential pressure using hydrogen gas through the electrolyte membrane to be measured, and calculate the amount of hydrogen gas permeated from the pressure change using the gas state equation. Specifically, first, the sample was set in the gas permeability measuring device, and the entire system was fully evacuated. Then, hydrogen was supplied so that the pressure of the entire system was about 50 kPa, and hydrogen was introduced from the high-pressure side hydrogen tank so that the pressure on the high-pressure side was about 150 kPa. The values ​​detected by the pressure gauge detecting the low-pressure side pressure and the pressure gauge detecting the high-pressure side pressure were read and recorded every 30 minutes. The mole number n was calculated from the pressure change over time on the high-pressure side and low-pressure side, using the relationship of the gas state equation (pV = nRT). Based on this, the gas permeability coefficient (mol m / m 2 ·s·Pa) was calculated.

[0056] In FIG. 3, as mentioned above, the gas permeability coefficient is P copm1 The gas permeability coefficient for P nano The ratio of P nano is a value obtained by measuring the gas permeability coefficient of the sample S1-S3 corresponding to the laminated proton conducting electrolyte membrane 10 of the embodiment having the nanosheet layer 16 as described above.copm1 is the value of the gas permeability coefficient of sample S4 corresponding to the bonded electrolyte membrane in which the first electrolyte membrane 12 and the second electrolyte membrane 14 are directly bonded by hot pressing without providing the nanosheet layer 16, measured as described above.

[0057] [Proton conductivity measurement] The proton pump method was used to measure the direct current proton conduction resistance in the membrane thickness direction. Here, for each of the laminated proton conductive electrolyte membrane samples S1 to S4, an anode was formed on one side and a cathode was formed on the other side to form a cell. In this method, hydrogen was supplied to the anode side, and the oxidation reaction of the following formula (7) was allowed to proceed at the anode and the oxidation reaction of the following formula (8) was allowed to proceed at the cathode, and the proton conductivity was calculated as follows.

[0058] H2 → 2H + + 2e - … (7) 2H + + 2e - → H2… (8)

[0059] Specifically, the evaluation cell used was a fuel cell evaluation cell FC-010-01H manufactured by Chemix Corporation, and the gasket used was a 0.160 mm thick gasket manufactured by Chemix Corporation. The electrochemical measurement system used was SP-300-10A manufactured by BioLogic Corporation, and INT-HYDLEC, a fuel cell evaluation system manufactured by Toyo Corporation. First, samples S1 to S4 (4 cm square) which were laminated proton conductive electrolyte membranes were A commercially available electrode with a diffusion layer was placed on both sides of the electrode. Here, a platinum catalyst was applied at 1.0 mg / cm on the gas diffusion layer GDL22BB manufactured by Chemix. 2 The electrode was then hot pressed at 135°C and 1 MPa for 1 minute to obtain an electrode with an area of ​​1 cm. 2Next, the prepared MEA was assembled into a cell, and hydrogen was supplied to the anode side at a flow rate of 1 NmL / min so that there was a large excess of hydrogen, and nitrogen was supplied to the cathode side at a flow rate of 2 NmL / min.

[0060] The total resistance was calculated from the proportional relationship of voltage to current density according to Ohm's law. However, the resistance calculated by this method includes resistance components due to activation overvoltage and concentration overvoltage, and resistance components other than the electrolyte membrane (cell, diffusion layer, catalyst layer, contact resistance, etc.). Therefore, MEAs were similarly produced using Nafion membranes of different thicknesses, and the relationship between the thickness and resistance of the Nafion membrane was measured at the same current density. By extrapolating to a thickness of zero, the resistance components other than these proton conduction resistances were estimated to be 0.037 Ω. This value was subtracted from the resistance value obtained by the proton pump method, and the proton conductivity in the lamination direction at room temperature and relative humidity of 100% RH was calculated according to the following formula (9). In formula (9), σ represents proton conductivity [mS / cm], R represents resistance [Ω], and A represents the electrode area [cm 2 ], and L [cm] represents the thickness of the laminated proton-conductive electrolyte membrane (50.8 μm for each sample of the examples).

[0061] σ=L / (R·A)×1000 … (9)

[0062] As mentioned above, in FIG. 3, the proton conductivity σ comp1 Proton conductivity σ nano The ratio of σ nano is the proton conductivity in the stacking direction of sample S2 or sample S3 corresponding to the stacked proton conducting electrolyte membrane 10 of the embodiment having the nanosheet layer 16 at room temperature and a relative humidity of 100% RH. comp1 is the proton conductivity in the stacking direction at room temperature and a relative humidity of 100% RH for sample S4, which corresponds to a bonded electrolyte membrane in which the first electrolyte membrane 12 and the second electrolyte membrane 14 are directly bonded by hot pressing without providing the nanosheet layer 16.

[0063] [Aspect ratio calculation] The thickness of the proton conductive nanosheet and the thickness of the nanosheet layer were measured as follows. That is, the same method as the method of forming the nanosheet layer 16 on the Nafion membrane during sample preparation was used to nanocoat a silicon single crystal substrate using the dispersion of the proton conductive nanosheet used to prepare samples S1-S3. The size and thickness of the obtained nanocoat layer were measured using an atomic force microscope to measure the thickness and particle size of the nanosheet layer. The aspect ratio was then calculated using the thickness and average particle size of the proton conductive nanosheet.

[0064] As mentioned above, the aspect ratio is also shown in Figure 3. The proton conductive nanosheet (graphene oxide) used in samples S1 and S2 had a single layer thickness of about 1.5 nm, including the length of the functional group, and the aspect ratio was about 13,300 when the average particle size was 20 μm. The proton conductive nanosheet (silicate nanosheet) used in sample S3 had a particle size of 100 nm-1000 nm, a thickness of 25-100 nm, and an aspect ratio of about 4-10.

[0065] [Evaluation Results] As shown in FIG. 3, the gas permeability coefficients of S1 to S3 are significantly smaller than those of sample S4, and the P nano / P copm The value of was 70% or less in all of the samples S1 to S3. In addition, S1 to S3 exhibited proton conductivity equivalent to that of the sample S4, and σ nano / σ copm The value of was more than 80% in both sample S2 and sample S3. It has been confirmed that by forming a laminated proton-conducting electrolyte membrane having a sandwich structure in which a first electrolyte membrane 12 and a second electrolyte membrane 14 are sandwiched, it is possible to achieve both high proton conductivity and low gas permeability.

[0066] The present disclosure is not limited to the above-mentioned embodiments, etc., and can be realized in various configurations without departing from the spirit of the present disclosure. For example, the technical features in the embodiments corresponding to the technical features in each form described in the Summary of the Invention column can be appropriately replaced or combined in order to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if a technical feature is not described as essential in this specification, it can be appropriately deleted.

[0067] The present disclosure can also be realized in the following forms. [Application example 1] A laminated proton-conducting electrolyte membrane, a first electrolyte membrane having proton conductivity, a nanosheet layer having a proton conductive nanosheet, and a second electrolyte membrane having proton conductivity are laminated in this order; the nanosheet layer is configured by assembling a plurality of the proton-conductive nanosheets in a plane direction of the nanosheet layer, The proton conductive nanosheet has proton conductivity in the stacking direction of the nanosheet layer. Laminated proton-conducting electrolyte membrane. [Application example 2] The laminated proton-conducting electrolyte membrane according to Application Example 1, The proton-conducting nanosheet is at least one selected from a graphene nanosheet, a graphene oxide nanosheet, a silicate nanosheet, an h-BN nanosheet, and a nitrogen-doped graphene nanosheet. Laminated proton-conducting electrolyte membrane. [Application example 3] The laminated proton-conducting electrolyte membrane according to Application Example 1 or 2, When the proton conductivity is measured under conditions of room temperature and a relative humidity of 100%, the proton conductivity σ in the stacking direction of the laminated proton-conducting electrolyte membrane is nano and a proton conductivity σ in the lamination direction of a bonded electrolyte membrane in which the first electrolyte membrane and the second electrolyte membrane are bonded without the nanosheet layer.comp1 When comparing with,σ comp1 σ for nano and the proton conductivity σ nano and a proton conductivity σ in the thickness direction of a single-layer electrolyte membrane which is the same type of electrolyte membrane as the first electrolyte membrane and the second electrolyte membrane and has a thickness equal to the total thickness of the first electrolyte membrane and the second electrolyte membrane. comp2 When comparing with,σ comp2 σ for nano At least one of the ratios is 80% or more, When the gas permeability coefficient is measured under the conditions of room temperature, relative humidity of 0% RH, and differential pressure of 100 kPa, the gas permeability coefficient P nano and the gas permeability coefficient P of the bonded electrolyte membrane comp1 When comparing with,P comp1 P for nano and the gas permeability coefficient P nano and the gas permeability coefficient P of the monolayer electrolyte membrane comp2 When comparing with,P comp2 P for nano At least one of the following ratios is 75% or less: Laminated proton-conducting electrolyte membrane. [Application example 4] The laminated proton-conducting electrolyte membrane according to any one of Application Examples 1 to 3, The aspect ratio, which is the ratio of the average particle size of the nanosheet to the thickness of the proton conductive nanosheet, is 10 to 10 7 is Laminated proton-conducting electrolyte membrane. [Application example 5] The laminated proton-conducting electrolyte membrane according to any one of Application Examples 1 to 4, A coverage rate, which is a ratio of an area of ​​a portion covered with the nanosheet layer to an area of ​​a surface of the first electrolyte membrane, is 70% or more and 99.9% or less. Laminated proton-conducting electrolyte membrane. [Application Example 6] A method for producing a laminated proton-conducting electrolyte membrane, comprising the steps of: A dispersion of proton-conducting nanosheets is prepared, While heating one of a first electrolyte membrane having proton conductivity and a second electrolyte membrane having proton conductivity, the dispersion liquid is dropped onto the one electrolyte membrane; After the dispersion liquid is dropped, the dropped dispersion liquid is removed from the one electrolyte membrane and the one electrolyte membrane is dried to form a nanosheet layer including the proton conductive nanosheet on the one electrolyte membrane; The other of the first electrolyte membrane and the second electrolyte membrane is laminated and bonded onto the nanosheet layer. A method for producing a laminated proton-conductive electrolyte membrane. [Explanation of symbols]

[0068] 10…Laminated proton-conducting electrolyte membrane 12...First electrolyte membrane 14…Second electrolyte membrane 16…Nanosheet layer

Claims

1. A laminated proton-conducting electrolyte membrane, a first electrolyte membrane having proton conductivity, a nanosheet layer having a proton conductive nanosheet, and a second electrolyte membrane having proton conductivity are laminated in this order; the nanosheet layer is configured by assembling a plurality of the proton-conductive nanosheets in a plane direction of the nanosheet layer, The proton conductive nanosheet has proton conductivity in the stacking direction of the nanosheet layer. A laminated proton-conducting electrolyte membrane.

2. The laminated proton-conducting electrolyte membrane according to claim 1, The proton-conducting nanosheet is at least one selected from a graphene nanosheet, a graphene oxide nanosheet, a silicate nanosheet, an h-BN nanosheet, and a nitrogen-doped graphene nanosheet. A laminated proton-conducting electrolyte membrane.

3. The laminated proton-conducting electrolyte membrane according to claim 1, When the proton conductivity is measured under conditions of room temperature and a relative humidity of 100% RH, the proton conductivity σ in the stacking direction of the stacked proton-conducting electrolyte membrane is nano and a proton conductivity σ in the lamination direction of a joined electrolyte membrane in which the first electrolyte membrane and the second electrolyte membrane are joined without the nanosheet layer. comp1 When comparing with,σ comp1 σ for nano and the proton conductivity σ nano and a proton conductivity σ in the thickness direction of a single-layer electrolyte membrane which is the same type of electrolyte membrane as the first electrolyte membrane and the second electrolyte membrane and has a thickness equal to the total thickness of the first electrolyte membrane and the second electrolyte membrane. comp2 When comparing with,σ comp2 σ for nano At least one of the ratios is 80% or more, When the gas permeability coefficient is measured under the conditions of room temperature, relative humidity of 0% RH, and differential pressure of 100 kPa, the gas permeability coefficient P nano and the gas permeability coefficient P of the bonded electrolyte membrane comp1 When comparing with,P comp1 P for nano and the gas permeability coefficient P nano and the gas permeability coefficient P of the monolayer electrolyte membrane comp2 When comparing with,P comp2 P for nano At least one of the ratios is 75% or less. Laminated proton-conducting electrolyte membrane.

4. The laminated proton-conducting electrolyte membrane according to claim 1, The aspect ratio, which is the ratio of the average particle size of the nanosheet to the thickness of the proton conductive nanosheet, is 10 to 10 7 is A laminated proton-conducting electrolyte membrane.

5. The laminated proton-conducting electrolyte membrane according to claim 1, A coverage rate, which is a ratio of an area of ​​a portion covered with the nanosheet layer to an area of ​​a surface of the first electrolyte membrane, is 70% or more and 99.9% or less. A laminated proton-conducting electrolyte membrane.

6. A method for producing a laminated proton-conducting electrolyte membrane, comprising the steps of: A dispersion of proton-conducting nanosheets is prepared, While heating one of a first electrolyte membrane having proton conductivity and a second electrolyte membrane having proton conductivity, the dispersion liquid is dropped onto the one electrolyte membrane; After the dispersion liquid is dropped, the dropped dispersion liquid is removed from the one electrolyte membrane. The one electrolyte membrane is dried to form a nanosheet layer including the proton-conductive nanosheet on the one electrolyte membrane; The other of the first electrolyte membrane and the second electrolyte membrane is laminated and bonded onto the nanosheet layer. A method for producing a laminated proton-conductive electrolyte membrane.

Citation Information

Patent Citations

  • Laminated electrolyte film, film electrode composite, water electrolysis cell, stack, water electrolysis apparatus, and hydrogen utilization system

    JP2019167619A